Fundamentals of Organic Chemistry - McMurry, John Simanek, Eric (THOMAS BROOKS/COLE, 2007)
Provides an introduction to the logic of organic chemistry. This book takes a modern approach: primary organization is by functional group, beginning with the simple (alkanes) and progressing to the more complex. It explains the fundamental mechanistic similarities of reactions.